2006
DOI: 10.1021/jo060765a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of 2-(Trifluoromethyl)- and 2-(Perfluoroalkyl)-2-hydroxy-2H-chromenes and Their Regiospecific Reaction with Silyl Enol Ethers

Abstract: The synthesis of substituted 2-(trifluoromethyl)- and 2-(perfluoroalkyl)-2-hydroxy-2H-chromenes 2a-o was achieved in good yields by intramolecular cyclization of 3-(perfluoroalkyl)-3-phenoxypropenals 1 in the presence of aluminum chloride. Then a Lewis acid mediated nucleophilic reaction with silyl enol ethers 3 proceeded with complete regiospecificity to afford 4-functional 2-(trifluoromethyl)- and 2-(perfluoroalkyl)-4H-chromenes 4a-p with high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 45 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…In previous articles [59,60,61,62,63,64,65] we have reported the synthesis of various perfluoroalkylated quinoline derivatives, by reacting perfluoroalkylated gem -iodoacyloxy derivatives 14 with substituted anilines 15 . Later we observed that the presence of a ketone in the medium leads to the formation of arylpyridiniums instead of quinolines; what suggested an interesting alternative to published synthetic methods, and led us to design a new and efficient synthesis of substituted 2-trifluoromethyl and 2-perfluoroalkyl- N -arylpyridinium derivatives 17 – 19 under mild reaction conditions and with very good yields.…”
Section: Introductionmentioning
confidence: 99%
“…In previous articles [59,60,61,62,63,64,65] we have reported the synthesis of various perfluoroalkylated quinoline derivatives, by reacting perfluoroalkylated gem -iodoacyloxy derivatives 14 with substituted anilines 15 . Later we observed that the presence of a ketone in the medium leads to the formation of arylpyridiniums instead of quinolines; what suggested an interesting alternative to published synthetic methods, and led us to design a new and efficient synthesis of substituted 2-trifluoromethyl and 2-perfluoroalkyl- N -arylpyridinium derivatives 17 – 19 under mild reaction conditions and with very good yields.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although introduction of fluorine atoms into organic compounds has been known as one of the best strategies for the enhancement or modification of their original biological activities [15,16,17,18,19], up to now there are limited reports on the preparation of 2-fluoroalkylated 2 H -chromenes. Laurent et al reported the synthesis of 2-(trifluoromethyl)- and 2-(perfluoroalkyl)-2-hydroxy-2 H -chromenes by intramolecular cyclization of 3-(perfluoroalkyl)-3-phenoxypropenals in the presence of aluminum chloride [20]. Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…27-A affords another intermediate 2 27. B, which upon intramolecular heterocyclization forms the desired chromene 276. one of the emerging fields of modern catalysis research.…”
mentioning
confidence: 99%